Water-based insulating paint and preparation method thereof
Through the combination of multiple insulating materials and dispersant compounding, combined with the self-repair mechanism of polyurethane microcapsules, the problem of poor dispersion of insulating materials in water-based insulating coatings is solved, the insulation performance and self-repair ability are improved, and the coating is uniform Sex and stability.
Patent Information
- Application Number
- CN202411424773.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-12
AI Technical Summary
During the use of existing water-based insulating coatings, there is a problem of poor dispersion uniformity between the insulating material and the coating matrix resin and pigment filler, which leads to poor insulation performance and affects its application.
Combination of a variety of insulating materials such as vapor phase silica, titanium dioxide, barium sulfate, mica powder, zinc phosphate and feldspar powder, combined with the combination of sulfonate and polycarboxylate dispersants to enhance the dispersion of coatings and improve the self-healing ability of the coating through the self-healing mechanism of polyurethane microcapsules.
It effectively improves the insulating performance and dispersion of the coating, reduces the use of a single insulating material, enhances the uniformity and self-repair ability of the coating, and avoids coating cracks and agglomeration.
Abstract
Description
Technical Field
[0001] The present application relates to the field of coating technology, and more specifically, to a water-based insulating coating and a preparation method thereof. Background Art
[0002] With the increasing awareness of environmental protection, water-based coatings have gradually attracted widespread attention due to their advantages such as environmental protection, non-toxicity and pollution-free. Among them, water-based insulating coatings, as a coating with excellent insulating properties, have broad application prospects in the fields of electricity, electronics, etc. However, there are many problems in the use of water-based insulating coatings currently on the market.
[0003] Traditional water-based insulating coatings mainly include components such as film-forming materials, pigments, fillers, additives and solvents. The insulating properties of the coatings are improved by adding appropriate amounts of insulating materials. However, excessive use of insulating materials can easily lead to problems such as the insulating materials being unable to be evenly dispersed with the coating matrix resin and pigments. Too little insulating material can easily lead to poor insulating properties of the coating, which in turn affects the application of the insulating coating. Summary of the invention
[0004] In order to improve the dispersibility problem of water-based insulating coatings while maintaining good insulating properties of the coatings, the present application provides a water-based insulating coating and a preparation method thereof.
[0005] In the first aspect, the present application provides a water-based insulating coating, which adopts the following technical solution: A water-based insulating coating comprises a component A and a component B, wherein the mass ratio of the component A to the component B is (7-9):1; the component A comprises the following raw materials in parts by weight: 100-150 parts of deionized water, 3-8 parts of bentonite, 3-8 parts of fumed silica, 40-80 parts of titanium dioxide, 90-110 parts of barium sulfate, 40-60 parts of mica powder, 60-80 parts of zinc phosphate, 40-60 parts of feldspar powder, 400-500 parts of epoxy emulsion, 3-5 parts of a substrate wetting agent, and 30-80 parts of a dispersant; the component B comprises the following raw materials in parts by weight: 40-60 parts of a curing agent and 40-60 parts of a solvent, wherein the dispersant comprises a sulfonate dispersant and a polycarboxylate dispersant.
[0006] By adopting the above technical scheme, fumed silica has a high specific surface area and low conductivity, titanium dioxide has excellent optical properties and chemical stability, can increase the volume resistance of the coating, and improve the insulating properties of the coating. Barium sulfate has a high resistivity, is non-conductive and has a high density, can improve the good filling effect, increase the thickness and density of the coating, and thus improve the insulating properties of the coating. Mica powder has a flaky physical structure and can form a physical barrier to hinder the transmission of charge; zinc phosphate can form a non-conductive network structure in the coating, thereby increasing the resistance of the coating and providing corrosion protection; feldspar powder can utilize low conductivity and chemical inertness to increase the thickness of the coating, reduce the penetration of current, and thus improve the insulating properties of the coating. This application reduces the penetration of current by utilizing the different insulating properties of a variety of insulating materials, so that the coating can maintain good insulating properties, while reducing the disadvantages of excessive use of a single insulating material and a single performance.
[0007] Bentonite and fumed silica can increase the viscosity of the coating, reduce the sedimentation and stratification of fillers in the coating system, reduce the dripping and flowing of the coating on the substrate surface, and improve the uniformity and adhesion of the coating. Fumed silica can enhance the cohesion of the coating, form a three-dimensional network structure in the coating system, make the coating tougher, and reduce the formation of coating cracks.
[0008] A sulfonate dispersant and a polycarboxylate dispersant are compounded and added to the coating as dispersants. The electrostatic effect of the sulfonate is used to impart surface charge to the filler particles in the coating system. The polycarboxylate dispersant can provide both electrostatic and steric hindrance. The combination of the two can enhance the stabilizing effect of charge dispersion, reduce the reaggregation of filler particles due to mutual attraction, reduce the phenomenon of particle agglomeration in the coating system, and improve the dispersibility of the coating system.
[0009] Preferably, the raw materials of component A of the water-based insulating coating also include the following components in parts by weight: 1-5 parts of a defoamer, 1-3 parts of a bactericide, 8-12 parts of an anti-flash rust agent, and 1-5 parts of a thickener.
[0010] Preferably, the sulfonate dispersant comprises the following components in parts by weight: 10-20 parts of sodium lignin sulfonate, 0.3-0.5 parts of initiator, 3-5 parts of polyethylene glycol monomethyl ether acrylate, and 5-8 parts of dimethylaminoethyl acrylate.
[0011] By adopting the above technical solution, sodium lignin sulfonate is a natural anionic dispersant that can better disperse filler particles and reduce the phenomenon of particle agglomeration in the coating. The polyethylene glycol segment in the macromolecular chain of polyethylene glycol monomethyl ether acrylate dissolves and stretches in water, which has a steric hindrance effect and improves the dispersibility and dispersion stability of the coating. Dimethylaminoethyl acrylate contains amino groups, which can be adsorbed on the surface of the coating substrate and can also be dissolved and dispersed in water, thereby achieving a dynamic balance, enabling the various components in the coating to be evenly dispersed and forming a firm and uniform coating on the surface of the substrate. The various components work together, and the sulfonate dispersant generated by the free radical polymerization reaction initiated by the initiator has a stable dispersion effect in the coating system, further reducing the agglomeration of particles.
[0012] Preferably, the preparation method of the sulfonate type dispersant comprises the following specific steps: dissolving and mixing sodium lignin sulfonate, polyethylene glycol monomethyl ether acrylate, dimethylaminoethyl acrylate and an initiator, heating to 70-80°C for reaction under the protection of nitrogen, and then cooling and evaporating to remove water vapor to obtain a sulfonate type dispersant.
[0013] Preferably, the dispersant further comprises polyurethane microcapsules, and the mass ratio of the polyurethane microcapsules, the sulfonate type dispersant and the polycarboxylate type dispersant is (0.3-0.5):1:1.
[0014] By adopting the above technical solution, polyurethane microcapsules are added to the coating system, and when the coating is scratched and cracked by external force, the polyurethane can react with the immersed water molecules to form cross-linked macromolecules and solidify at the cracked part of the coating, thereby repairing the cracks and improving the self-repairing ability of the coating. At the same time, compounding the polyurethane microcapsules with sulfonate dispersants and polycarboxylate dispersants can promote the uniform dispersion of the polyurethane microcapsules in the coating system, thereby improving the uniformity of the self-repairing effect of the coating and reducing the phenomenon of coating cracking.
[0015] Preferably, the core-to-wall ratio of the polyurethane microcapsule is 0.5-0.8, wherein the wall material is carboxymethyl cellulose, and the core material comprises the following raw materials in parts by weight: 30-40 parts of polyoxypropylene polyol, 50-60 parts of isocyanate, and 1-3 parts of 2,2-dihydroxymethylpropionic acid.
[0016] By adopting the above technical solution, biodegradable carboxymethyl cellulose is used as the wall material, which is easier to disperse in water-based coatings. The carboxyl group of carboxymethyl cellulose is used to provide negative charges to prevent the aggregation of polyurethane microcapsules and improve the dispersibility of polyurethane microcapsules. On the other hand, when the coating is used normally, carboxymethyl cellulose as a wall material can promote the polyurethane microcapsules to have good stability. The high surface activity of carboxymethyl cellulose can help disperse the particles in the coating system, while improving the adhesion between the coating and the substrate and reducing the shedding and cracking of the coating.
[0017] Preferably, the preparation method of the polyurethane microcapsule comprises the following specific steps: dissolving carboxymethyl cellulose in advance to form a wall material solution, dissolving and mixing polyoxypropylene polyol and isocyanate, heating and reacting, then adding 2,2-dihydroxymethyl propionic acid and heating to 70-90°C to continue the reaction to obtain an aqueous polyurethane emulsion, mixing the aqueous polyurethane emulsion and the wall material solution, stirring at high speed, and spray drying to obtain the polyurethane microcapsule.
[0018] In a second aspect, the present application provides a method for preparing a water-based insulating coating, using the following technical solution: A preparation method of a water-based insulating coating comprises the following specific steps: deionized water, a dispersant, bentonite and fumed silica are mixed, dispersed at high speed, titanium dioxide, barium sulfate, mica powder, zinc phosphate and feldspar powder are added and ground, and finally epoxy emulsion and a substrate wetting agent are added and mixed, stirred evenly to form component A; a curing agent and a solvent are mixed to form component B, and component A and component B are mixed according to a proportion to form a water-based insulating coating.
[0019] By adopting the above technical solution, the insulation properties of various types of insulating materials are utilized to improve the insulation performance of the coating, and the phenomenon of particle agglomeration caused by excessive use of a single insulating material is reduced. At the same time, through the compounding effect of sulfonate dispersants and polycarboxylate dispersants, the dispersion effect of the coating system is improved, and the re-agglomeration of dispersed particles in the coating system is reduced.
[0020] Preferably, deionized water, dispersant, defoamer, bentonite and fumed silica are mixed and dispersed at high speed, and then titanium dioxide, barium sulfate, mica powder, zinc phosphate and feldspar powder are added and ground, and finally epoxy emulsion, substrate wetting agent, bactericide, anti-flash rust agent and thickener are added and mixed, and stirred evenly to form component A; the curing agent and the solvent are mixed to form component B, and component A and component B are mixed according to the ratio to form a water-based insulating coating.
[0021] In summary, this application has the following beneficial effects: 1. Since the present application adopts a compound of multiple insulating materials including fumed silica, titanium dioxide, barium sulfate, mica powder, zinc phosphate and feldspar powder, the problem of poor insulation effect of a single insulating material is avoided, the insulation performance of the coating is improved, and the phenomenon of agglomeration caused by excessive use of a single insulating material is reduced, and the dispersibility of the coating system is improved. Sulfonate dispersants and polycarboxylate dispersants are compounded as dispersants to enhance the stability of the particle dispersion effect, reduce the phenomenon of particle agglomeration in the coating system, and improve the uniformity of the coating.
[0022] 2. The polyurethane microcapsules made of carboxymethyl cellulose as the wall material and polyurethane as the core material in this application can cross-link and solidify with the immersed water molecules at the cracks of the coating to repair the cracks and enhance the self-repairing ability and crack resistance of the coating. At the same time, the use of carboxymethyl cellulose can improve the dispersion effect of polyurethane microcapsules in the coating system and reduce the aggregation between polyurethane microcapsules. DETAILED DESCRIPTION
[0023] The present application is further described in detail below in conjunction with embodiments.
[0024] The substrate wetting agent is the organic silicon wetting agent Greesol H87.
[0025] The flash rust inhibitor is NALZIN FA-179.
[0026] The defoaming agent is TEGO Foamex-810.
[0027] The epoxy emulsion is Banco2060H.
[0028] The curing agent is Banco901.
[0029] The solvent is ethylene glycol butyl ether.
[0030] The thickener is polyurethane thickener RM-12W.
[0031] The fungicide is MBS.
[0032] Preparation Example 1 The sulfonate dispersant comprises the following raw materials in parts by weight: 15 kg sodium lignin sulfonate, 0.4 kg initiator, 4 kg polyethylene glycol monomethyl ether acrylate, and 7 kg dimethylaminoethyl acrylate, wherein the initiator is benzoyl peroxide.
[0033] The preparation method of the sulfonate dispersant comprises the following specific steps: Sodium lignin sulfonate, polyethylene glycol monomethyl ether acrylate, dimethylaminoethyl acrylate and an initiator are dissolved in deionized water in advance to form a sulfonate mixed solution with a sodium lignin sulfonate concentration of 1 mol / L. The mixture is then heated to 75°C under the protection of nitrogen, reacted for 4 hours, cooled to room temperature, and the water is evaporated to obtain a sulfonate type dispersant.
[0034] Preparation Example 2 The difference between Preparation Example 2 and Preparation Example 1 is that the amount of sodium lignin sulfonate used in the sulfonate type dispersant raw material is 10 kg, the amount of initiator used is 0.3 kg, the amount of polyethylene glycol monomethyl ether acrylate used is 3 kg, and the amount of dimethylaminoethyl acrylate used is 5 kg.
[0035] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the amount of sodium lignin sulfonate used in the sulfonate type dispersant raw material is 20 kg, the amount of initiator used is 0.5 kg, the amount of polyethylene glycol monomethyl ether acrylate used is 5 kg, and the amount of dimethylaminoethyl acrylate used is 8 kg.
[0036] Preparation Example 4 The polyurethane microcapsule comprises a core material and a wall material, wherein the mass ratio of the core material to the wall material is 0.7, wherein the wall material is carboxymethyl cellulose, and the core material comprises the following raw materials in parts by weight: 35 kg of polyoxypropylene polyol, 55 kg of isocyanate, and 2 kg of 2,2-dimethylol propionic acid, wherein the isocyanate is hexamethylene diisocyanate, and the polyoxypropylene polyol is polyoxypropylene glycol DL-400.
[0037] The preparation method of polyurethane microcapsules comprises the following specific steps: After dehydrating the polyoxypropylene polyol, it is mixed and dissolved with isocyanate, heated to 60°C and reacted for 1 hour, then 2,2-dihydroxymethylpropionic acid is added and heated to 80°C for reaction for 3 hours, and vacuum degassing is performed to obtain an aqueous polyurethane emulsion; then carboxymethyl cellulose is dissolved in dichloromethane to form a wall material solution, the aqueous polyurethane emulsion and the wall material solution are mixed, stirred at a speed of 2000rpm for 10 minutes, and spray-dried to obtain polyurethane microcapsules.
[0038] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 4 is that the amount of polyoxypropylene polyol used in the polyurethane microcapsule core material is 30 kg, the amount of isocyanate used is 50 kg, and the amount of 2,2-dihydroxymethylpropionic acid used is 1 kg.
[0039] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 4 is that the amount of polyoxypropylene polyol used in the polyurethane microcapsule core material is 40 kg, the amount of isocyanate used is 60 kg, and the amount of 2,2-dihydroxymethylpropionic acid used is 3 kg.
[0040] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 4 is that an equal amount of polyether diol is used in the raw material of the polyurethane microcapsule core material instead of polyoxypropylene polyol, wherein the molecular weight of the polyether diol is 4000. Example Example
[0041] This embodiment provides a water-based insulating coating, including component A and component B, the mass ratio of component A to component B is 8:1, component A includes the following raw materials in parts by weight: 130kg of deionized water, 5kg of bentonite, 5kg of fumed silica, 60kg of titanium dioxide, 100kg of barium sulfate, 50kg of mica powder, 70kg of zinc phosphate, 50kg of feldspar powder, 450kg of epoxy emulsion, 4kg of substrate wetting agent, and 55kg of dispersant. The dispersant is a mixture of a polycarboxylate dispersant and a sulfonate dispersant, the mass ratio of the polycarboxylate dispersant to the sulfonate dispersant is 1:1, the polycarboxylate dispersant is purchased from sodium polyaspartate PASP of Shandong Taihe Technology Co., Ltd., and the sulfonate dispersant is sodium dodecylbenzene sulfonate.
[0042] The preparation method of the water-based insulating coating comprises the following specific steps: Deionized water, dispersant, bentonite and fumed silica are mixed, dispersed at a speed of 500 rpm for 10 minutes, and then titanium dioxide, barium sulfate, mica powder, zinc phosphate and feldspar powder are added and dispersed for another 10 minutes to form a mixture. The mixture is then ground to a particle size of ≤5 μm, and finally epoxy emulsion and substrate wetting agent are added and mixed, and stirred to form component A; a curing agent and a solvent are mixed to form component B, and component A and component B are mixed evenly according to a ratio to form a water-based insulating coating. Example
[0043] The difference between Example 2 and Example 1 is that the mass ratio of component A to component B in the water-based insulating coating is 7:1. Example
[0044] The difference between Example 3 and Example 1 is that the mass ratio of component A to component B in the water-based insulating coating is 9:1. Example
[0045] The difference between Example 4 and Example 1 is that the raw materials of component A of the water-based insulating coating also include 3kg of defoaming agent, 2kg of bactericide, 10kg of anti-flash rust agent, and 3kg of thickener.
[0046] The preparation method of the water-based insulating coating comprises the following specific steps: Deionized water, dispersant, defoamer, bentonite and fumed silica are mixed, dispersed at a speed of 500 rpm for 10 minutes, and then titanium dioxide, barium sulfate, mica powder, zinc phosphate and feldspar powder are added and dispersed for another 10 minutes to form a mixture. The mixture is then ground to a particle size of ≤5 μm, and finally epoxy emulsion, substrate wetting agent, bactericide, anti-flash rust agent and thickener are added and mixed, and stirred evenly to form component A; a curing agent and a solvent are mixed to form component B, and components A and B are evenly mixed according to a ratio to form a water-based insulating coating. Example
[0047] The difference between Example 5 and Example 4 is that the raw material of component A of the water-based insulating coating is The usage of deionized water is 100kg, the usage of bentonite is 3kg, the usage of fumed silica is 8kg, the usage of titanium dioxide is 40kg, the usage of barium sulfate is 90kg, the usage of mica powder is 60kg, the usage of zinc phosphate is 60kg, the usage of feldspar powder is 60kg, the usage of epoxy emulsion is 400kg, the usage of substrate wetting agent is 5kg, the usage of dispersant is 30kg, the usage of defoaming agent is 1kg, the usage of bactericide is 3kg, the usage of anti-flash rust agent is 12kg, and the usage of thickener is 1kg. Example
[0048] The difference between Example 6 and Example 4 is that the amount of deionized water used in the raw materials of component A of the water-based insulating coating is 150 kg, the amount of bentonite used is 8 kg, the amount of fumed silica used is 3 kg, the amount of titanium dioxide used is 80 kg, the amount of barium sulfate used is 110 kg, the amount of mica powder used is 40 kg, the amount of zinc phosphate used is 80 kg, the amount of feldspar powder used is 40 kg, the amount of epoxy emulsion used is 500 kg, the amount of substrate wetting agent used is 3 kg, the amount of dispersant used is 80 kg, the amount of defoaming agent used is 5 kg, the amount of bactericide used is 1 kg, the amount of anti-flash rust agent used is 8 kg, and the amount of thickener used is 5 kg. Example
[0049] The difference between Example 7 and Example 1 is that the sulfonate dispersant in the raw material dispersant of component A of the water-based insulating coating is derived from Preparation Example 1. Example
[0050] Example 8 differs from Example 1 in that the sulfonate dispersant in the raw material dispersant of component A of the water-based insulating coating comes from Preparation Example 2. Example
[0051] The difference between Example 9 and Example 1 is that the sulfonate dispersant in the raw material dispersant of component A of the water-based insulating coating is derived from Preparation Example 3. Example
[0052] The difference between Example 10 and Example 7 is that the raw material dispersant of component A of the water-based insulating coating also includes polyurethane microcapsules, wherein the polyurethane microcapsules are derived from Preparation Example 4, and the mass ratio of the polyurethane microcapsules, the sulfonate dispersant and the polycarboxylate dispersant is 0.4:1:1. Example
[0053] The difference between Example 11 and Example 7 is that the polyurethane microcapsules in the raw material dispersant of component A of the water-based insulating coating are derived from Preparation Example 5. Example
[0054] The difference between Example 12 and Example 7 is that the polyurethane microcapsules in the raw material dispersant of component A of the water-based insulating coating are derived from Preparation Example 6. Example
[0055] The difference between Example 13 and Example 7 is that the polyurethane microcapsules in the raw material dispersant of component A of the water-based insulating coating are derived from Preparation Example 7.
[0056] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no polycarboxylate dispersant is used in the raw material dispersant of component A of the water-based insulating coating.
[0057] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that no dispersant is used in the raw material of component A of the water-based insulating coating. Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that an equal amount of mica powder is used in the raw materials of component A of the water-based insulating coating to replace fumed silica, titanium dioxide, barium sulfate, zinc phosphate and feldspar powder.
[0058] The following performance tests were performed on the water-based insulating coatings provided in Examples 1-13 and Comparative Examples 1-3 of the present application, and the specific test results are shown in Table 1.
[0059] 1. Insulation performance The volume resistivity of the coating prepared in this application was tested with reference to the standard of Part 2 of GB / T 31838.2-2019 "Dielectric and Resistive Properties of Solid Insulating Layer Materials"; the electrical strength of the coating prepared in this application was tested with reference to the standard of HG / T3330-2012 "Test Method for Breakdown Strength of Insulating Paint Films".
[0060] 2. Self-repair capability With reference to the standard of JC / T 975-2005 "Waterproof Coatings for Roads and Bridges", the self-repairing time of cracks of about 0.5 mm of the coating prepared in this application was tested.
[0061] 3. Coating appearance The coating prepared in the present application was coated on a sandblasted plate with an average coating thickness of 0.2 mm. The coating was placed in a 25° C. constant temperature box to dry for 48 hours, and whether the coating was flat and smooth was observed.
[0062] Table 1: Performance test results data table Example <![CDATA[Volume resistivity (*10 12 / Ω•m)]]> Electric strength (MV / m) Self-repair time (s) Coating appearance Example 1 1.23 33.4 21 Flat and smooth Example 2 1.10 32.5 23 / Example 3 1.21 33.1 / / Example 4 1.35 35.2 / / Example 5 1.30 34.1 / / Example 6 1.33 34.8 / / Example 7 1.63 39.8 / Smooth and smooth, good self-leveling effect Example 8 1.59 38.6 / Smooth and smooth, good self-leveling effect Example 9 1.62 39.3 / Smooth and smooth, good self-leveling effect Example 10 1.89 43.1 11 / Embodiment 11 1.81 42.5 13 / Example 12 1.86 42.7 12 / Example 13 1.74 41.9 15 / Comparative Example 1 1.05 30.8 40 The surface is flat but slightly Comparative Example 2 0.98 29.7 60 Rough, uneven surface Comparative Example 3 0.05 17.6 Cracks cannot be repaired The granular texture is obvious From the performance test results, it can be seen that the water-based insulating coating prepared in this application can maintain good insulation performance under the synergistic effect of each component, and the dispersibility of each component in the coating system is good. In Examples 1-6, the usage amount of each component is different, and the comprehensive performance of Example 4 is better.
[0063] In Examples 7-9, a sulfonate dispersant synthesized from sodium lignin sulfonate, polyethylene glycol monomethyl ether acrylate, and dimethylaminoethyl acrylate was used. From the performance test results, it can be seen that the coating surface is smoother and more uniform, and the self-leveling effect is better, which further illustrates that the sulfonate dispersant prepared in the present application is added to the coating system to promote better and more stable dispersion performance of the coating.
[0064] In Examples 10-12, polyurethane microcapsules are also added to the dispersant. From the performance test results, it can be seen that the self-repairing ability of the coating is significantly increased, which can promote the self-healing of cracks, reduce the expansion of coating cracks, and improve the stability of the coating. By comparing Example 13 with Example 10, it can be seen that the polyurethane microcapsules prepared using different polyols have different promoting effects on the self-repairing ability of the coating. Example 13 uses polyether diols, and the self-repairing ability of the coating decreases. This may be because compared with polyether polyols, polyoxypropylene polyols have better flexibility, which enables the prepared polyurethane to have stronger elastic toughness, thereby improving the anti-cracking performance of the coating, reducing the expansion of coating cracks, and improving the self-repairing ability of the coating.
[0065] By comparing Comparative Examples 1-3 with Example 1, it can be seen that Comparative Example 1 uses a single dispersant, while Comparative Example 2 does not use a dispersant. From the performance test results, it can be seen that the dispersion effect of the coating is not good. This may be because after the particles are dispersed by physical dispersion or a single dispersant, the particles in the coating system re-aggregate during the storage of the coating, resulting in agglomeration. In Comparative Example 3, a single mica powder is used to replace other types of insulating materials. From the performance test results, it can be seen that the insulation performance and dispersion effect of the coating are greatly reduced, the coating has obvious granularity, and a complete coating cannot be formed. It further illustrates that the present application uses multiple types of insulating materials to improve the performance of the coating in all directions, while maintaining good dispersion performance in the coating system.
[0066] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A water-based insulating coating, characterized in that: The invention comprises component A and component B, wherein the mass ratio of component A to component B is (7-9):1; component A comprises the following raw materials in parts by weight: 100-150 parts of deionized water, 3-8 parts of bentonite, 3-8 parts of fumed silica, 40-80 parts of titanium dioxide, 90-110 parts of barium sulfate, 40-60 parts of mica powder, 60-80 parts of zinc phosphate, 40-60 parts of feldspar powder, 400-500 parts of epoxy emulsion, 3-5 parts of substrate wetting agent, and 30-80 parts of dispersant; component B comprises the following raw materials in parts by weight: 40-60 parts of curing agent and 40-60 parts of solvent, and the dispersant comprises a sulfonate dispersant and a polycarboxylate dispersant.
2. The water-based insulating coating according to claim 1, characterized in that: The raw materials of component A of the water-based insulating coating also include the following components in parts by weight: 1-5 parts of a defoamer, 1-3 parts of a bactericide, 8-12 parts of an anti-flash rust agent, and 1-5 parts of a thickener.
3. The water-based insulating coating according to claim 1, characterized in that: The sulfonate dispersant comprises the following components in parts by weight: 10-20 parts of sodium lignin sulfonate, 0.3-0.5 parts of initiator, 3-5 parts of polyethylene glycol monomethyl ether acrylate, and 5-8 parts of dimethylaminoethyl acrylate.
4. The water-based insulating coating according to claim 3, characterized in that: The preparation method of the sulfonate dispersant comprises the following specific steps: dissolving and mixing sodium lignin sulfonate, polyethylene glycol monomethyl ether acrylate, dimethylaminoethyl acrylate and an initiator, heating to 70-80° C. for reaction under the protection of nitrogen, and then cooling and evaporating to remove water vapor to obtain the sulfonate dispersant.
5. The water-based insulating coating according to claim 1, characterized in that: The dispersant further comprises polyurethane microcapsules, and the mass ratio of the polyurethane microcapsules, the sulfonate type dispersant and the polycarboxylate type dispersant is (0.3-0.5):1:
1.
6. The water-based insulating coating according to claim 5, characterized in that: The core-to-wall ratio of the polyurethane microcapsule is 0.5-0.8, wherein the wall material is carboxymethyl cellulose, and the core material comprises the following raw materials in parts by weight: 30-40 parts of polyoxypropylene polyol, 50-60 parts of isocyanate, and 1-3 parts of 2,2-dihydroxymethyl propionic acid.
7. The water-based insulating coating according to claim 6, characterized in that: The preparation method of the polyurethane microcapsule comprises the following specific steps: dissolving carboxymethyl cellulose in advance to form a wall material solution, dissolving and mixing polyoxypropylene polyol and isocyanate, heating and reacting, then adding 2,2-dihydroxymethyl propionic acid and heating to 70-90° C. to continue the reaction to obtain an aqueous polyurethane emulsion, mixing the aqueous polyurethane emulsion and the wall material solution, stirring at a high speed, and spray drying to obtain the polyurethane microcapsule.
8. A method for preparing a water-based insulating coating according to any one of claims 1 to 7, characterized in that: The method comprises the following specific steps: mixing deionized water, a dispersant, bentonite and fumed silica, dispersing at high speed, then adding titanium dioxide, barium sulfate, mica powder, zinc phosphate and feldspar powder for grinding, and finally adding epoxy emulsion and a substrate wetting agent for mixing and stirring evenly to form component A; mixing a curing agent and a solvent to form component B, and mixing component A and component B according to a proportion to form a water-based insulating coating.
9. The method for preparing the water-based insulating coating according to claim 8, characterized in that: Deionized water, dispersant, defoamer, bentonite and fumed silica are mixed and dispersed at high speed. Titanium dioxide, barium sulfate, mica powder, zinc phosphate and feldspar powder are then added and ground. Finally, epoxy emulsion, substrate wetting agent, bactericide, anti-flash rust agent and thickener are added and mixed. The mixture is stirred evenly to form component A. The curing agent and solvent are mixed to form component B. Component A and component B are mixed according to the proportion to form a water-based insulating coating.
Citation Information
Patent Citations
Highly corrosion-resistant anticorrosive coating and preparation method therefor
CN105295651A
Water-based single-component epoxy anticorrosive paint for coating automobile plate spring and preparation method thereof
CN111320917A
Water-based oil-resistant temperature-resistant insulating antirust primer and application thereof
CN118638462A
Cited By
Ultraviolet curing water-based insulating paint and preparation method thereof
CN119639311A
